Beta-Blockers of Different Generations: Features of Influence on the Disturbances of Myocardial Energy Metabolism in Doxorubicin-Induced Chronic Heart Failure in Rats - Belenichev, I. F.; Goncharov, O. V.; Bukhtiyarova, N. V.; Kuchkovskyi, O. M.; Ryzhenko, V. P.; Makyeyeva, L. V.; Oksenych, V.; Kamyshnyi, O.; Бєленічев, Ігор Федорович; Гончаров, Олексій Валентинович; Бухтіярова, Ніна Вікторівна; Кучковський, Олег Миколайович; et al. (My University, 2024)
Beta-blockers are first-line drugs in the treatment of chronic heart failure (CHF). However, there is no consensus on the specific effects of the beta-blockers of the I-III generation on energy metabolism in CHF. The aim of this study is to conduct a study of beta-blockers of different generations on myocardial energy metabolism in experimental CHF. CHF was modeled in white outbred rats by administering doxorubicin. The study drugs were administered intragastrically—new drug Hypertril (1-(β-phenylethyl)-4-amino-1,2,4-triazolium bromide)-3.5 mg/kg, Metoprolol—15 mg/kg, Nebivolol −10 mg/kg, Carvedilol 50 mg/kg, and Bisoprolol, 10 mg/kg. In the myocardium, the main indices of energy metabolism were determined—ATP, ADP, AMP, malate, lactate, pyruvate, succinate dehydrogenase (SDH) activity, and NAD-dependent malate dehydrogenase (NAD-MDH) activity. Traditional second-generation beta-blockers (Metoprolol and Bisoprolol) did not affect the studied indices of energy metabolism, and third-generation beta-blockers with additional properties— Carvedilol and, especially, Nebivalol and Hypertril—improved myocardial energy metabolism. The obtained results will help to expand our understanding of the effect of beta-blockers of various generations used to treat cardiovascular diseases on energy metabolism, and are also an experimental justification for the practical choice of these drugs in the complex therapy of CHF.
Keywords: chronic heart failure; beta-blockers; energy metabolism; mitochondria; Hypertril